Melatonin delivery from PCL scaffold enhances glycosaminoglycans deposition in human chondrocytes – Bioactive scaffold model for cartilage regeneration. (December 2020) - S., Manjunath Kamath; Rao, Subha Krishna; D., Jaison; K., Sridhar; N., Kasthuri; V., Gopinath; P., Sivaperumal; S., Shantanu Patil
Graphical abstract: Highlights: Melatonin albumin nanoparticle (MNP) embedded polycaprolactone scaffold fabricated. Controlled release observed for 22 days. MNP concentration modulated melatonin release from scaffolds. Significant elevation in Glycosaminoglycans - Human chondrocytes. Diffusion & dissolution mechanism of drug release – mathematical models. Abstract: The therapeutic potential of an engineered cartilage construct can be enhanced by sustained delivery of chondrogenic drug like melatonin from 3D porous scaffolds embedded with melatonin loaded bovine serum albumin nanoparticles (MNP). In this study, MNP was synthesized and loaded into polycaprolactone (PCL) scaffolds. 12 % (w/v) and 10 % (w/v) PCL scaffolds were fabricated with different concentrations of MNP. X- ray diffraction and Raman analysis of MNP and scaffolds revealed amorphization of melatonin which is highly desired in drug delivery applications. Additionally, Fourier Transform Infrared spectroscopic analysis confirmed the drug to be chemically inert to fabrication process. Field emission scanning electron microscopic analysis suggested highly interlinked porous scaffold (diameter 50 μm – 300 μm) and MNP diameters in the range of 110−200 nm. Importantly, UV spectrophotometric analysis showed that all groups of scaffolds showed sustained release for 21 days, wherein MNP concentration had an influence on release behaviour of melatonin from scaffolds. Drug release kinetics studied using mathematical models revealed, diffusion and dissolution mechanism of release. Furthermore, in vitro evaluation of MNP loaded scaffolds with Human chondrocytes for 21 days increased glycosaminoglycans deposition significantly. In brief, sustained release of melatonin from polycaprolactone scaffolds increased the therapeutic potential of the engineered construct.